DISCUSSION GAMES AS AN INNOVATION TO IMPROVE THE SPEAKING ABILITY - admin admin; Putri Marina Sari (Universitas Muhammadiyah Gresik, 2012)
Speaking is one of the skills that have to be mastered by the learners in teaching learning process. Whenever students want to speak, they always feel afraid of making mistake. Based on the problem above, the teachers have to find the appropriate technique or media. Discussion games can help the students to improve their speaking ability. The main intention of discussion games is, to get the students to talk and to stimulate their interest and imagination. By using discussion games the teacher can also use this game to improve the atmosphere in the class and help students cooperate better with each other.